Aplicação de jogos no ensino de Geometria plana - Valente, Adriano Felix (2022)
The new generations of students, called digital, have presented a growing challenge to teachers. Early exposure to a large amount of information has caused a deep change in students' behavior. Traditional teaching, based on lectures in which students passively watch the teacher come up with content, has not comply with this audience. New methodologies have been researched in an attempt to reach young people through a teaching paradigm that takes the role of protagonist from the teacher, assigning it to the students. Among the various existing active methodologies, this work highlights Team-Based Learning and Game-Based Learning. The first is a variation of the Flipped-Classroom methodology and the second deals with the use of games supporting the teaching/learning process, reinforcing content or preparing for future classes. A proposal for a teaching plan is presented to reinforce the study of proportions between areas of different polygons, following the guidelines of the new brazilian National Curricular Common Base, specifically those of the final years of elementary school